Nature's Arsenal: Exploring the Anticancer Properties of Bioactive Compounds from Natural Sources - Thakur, Tamanna; Saharan, Renu; Beniwal, Suresh Kumar; Dahiya, Preeti; Verma, Inderjeet; Dhankhar, Sanchit; Chauhan, Samrat; Yasmin, Sabina; Singh, Thakur Gurjeet (Current Bioactive Compounds, 2025)
Considering that cancer is a disease that affects people all over the world, there has been a movement in the focus of scientific and research efforts towards substances that are acquired from natural sources. It has been demonstrated that the identification of pharmaceuticals originating from plants has proven to be particularly beneficial in the process of producing anticancer therapies such as vincristine, vinblastine, paclitaxel, and irinotecan. Additionally, marine sources have provided substances such as cytarabine and aplidine, and microbes have developed important drugs such as dactinomycin, doxorubicin, and bleomycin with their anticancer qualities. The purpose of this review is to highlight the fact that active components derived from natural sources present significant opportunities for the discovery of not only completely new categories of anticancer medicines but also novel precursor chemical compounds. The purpose of this article is to review naturally isolated anticancer medications from a wide range of agents that can be derived from a wide range of natural resources, such as bacteria, marine organisms, and plants.
Keywords: aplidine